Retrato de Auguste Gabriel Godefroy: Educação e Infância na Obra de Chardin - Ferreira, Lara Barbosa (2018)
This research analyzes the work Portrait of Auguste Gabriel Godefroy (1741) by the French artist Jean-Siméon Chardin. The painting belongs to the São Paulo Art Museum Assis Chateaubriand - MASP - and we are interested in being related to the discussion about education in childhood in the eighteenth century, in particular the child between homework and fun. It is proposed to understand the multiple senses of this painting, the relations with French painting of the eighteenth century, the repercussion of such an image and its apprehensions. The issues surrounding the acquisition of the painting by the MASP, and the critical and reception literature will also be addressed. The aim is also to understand the approach to the theme by different artists of the same period, as well as the appropriation of the image and the central motto, the boy and the top, multiplied in supports like book covers, posters and cinematographic productions.